Delovnopravni vidiki učinkovitega uresničevanja pravice do izobraževanja in usposabljanja delavcev - Franca, Valentina (Delavci in delodajalci, 2021)
Education and training in the workplace have become even more important in the wake of the epidemic, especially in terms of mastering digital skills. Although the right to education and training of workers is regulated in both international and national legal acts, in Slovenia we record a relatively low percentage of workers participating in education and training; this is even more true for precarious workers. As laid down in the European Social Charter, it is necessary to ensure the effective exercise of this right, which must be promoted by both workers and employers and their representatives.
Keywords: delavci; delodajalec; digital competences; digitalne veščine; education; employers; izobraževanje; training; usposabljanje; workers